Digital Diffusion of Research: Ongoing Studies & Potentials - Harrington, J. Brooke; Bing, Judith (ARCC Conference Repository, 2013)
In the study of vernacular architecture, verification of physical space and understanding social, cultural, and economic contexts are of central importance. Today the challenge is to create new ways toshare findings and invite dialogue. Our studies of early wooden structures in the Balkans have yielded publications and exhibitions on regions and buildings as well as our drawings and photographs. Today the Internet includes an increasing number of sites with images of vernacular buildings that survive orare being restored. A number of preservation institutes and other organizations are developing websites to reveal these cultural treasures. Within this context, we are working to produce an open access site with a flexible format to provide information that crosses national and cultural borders, that in some cases are more rigid as countries in the Balkans reinterpret their cultural heritage and their artifacts. This shift in presentation media and transformation in historical interpretations demand that we revisit our research and the way it is disseminated. This paper focuses on two aspects. First, it will present examples of misinformation created as national entities begin to redefine their identities. These include situations where historians, scholars, politicians andjournalists have created views that are more fantasy than actual. Second, we will show strategies that we are implementing in our website to allow others to view a database with bibliographic notes of Balkan vernacular architectural artifacts that cover the period from the 17th through the last part of the 20th century. The website describes visited and studied buildings, locates these geographically, and will include an interactive database to allow access to images and information about similar building types across the Balkan peninsula, and will allow others to contribute.